2007
DOI: 10.1359/jbmr.070210
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine, Folate, and Vitamin B12 and the Risk of Hip Fracture: The Hordaland Homocysteine Study

Abstract: Homocysteine and related factors were evaluated as risk factors for subsequent hip fractures among 4766 elderly men and women. High levels of homocysteine and low levels of folate predicted fracture, whereas vitamin B 12 and genotypes were not related to fracture risk. High homocysteine may be a modifiable risk factor for hip fracture.Introduction: Elevated plasma total homocysteine (tHcy) and deficiencies of folate and vitamin B 12 are associated with risk of osteoporosis and fracture. We examined whether pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
2
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 52 publications
1
99
2
11
Order By: Relevance
“…In 2004, two landmark studies performed in the Netherlands and the USA produced consistent findings in terms of the magnitude of increased risk of fracture associated with mild elevations in homocysteine (36,37) . In subsequent years, further studies from the USA, the Netherlands and Norway similarly demonstrated increases in fracture risk associated with elevated homocysteine concentrations (31)(32)(33)35) . Confirming these findings, a recent meta-analysis involving nine prospective studies and 14 863 participants reported a relative risk of 1.59 (95 % CI 1.30, 1.96) and 1.67 (95 % CI 1.17, 2.38) for all fractures and hip fractures, respectively, in those within the highest homocysteine quartile compared with the lowest (30) .…”
Section: Evidence From Observational Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…In 2004, two landmark studies performed in the Netherlands and the USA produced consistent findings in terms of the magnitude of increased risk of fracture associated with mild elevations in homocysteine (36,37) . In subsequent years, further studies from the USA, the Netherlands and Norway similarly demonstrated increases in fracture risk associated with elevated homocysteine concentrations (31)(32)(33)35) . Confirming these findings, a recent meta-analysis involving nine prospective studies and 14 863 participants reported a relative risk of 1.59 (95 % CI 1.30, 1.96) and 1.67 (95 % CI 1.17, 2.38) for all fractures and hip fractures, respectively, in those within the highest homocysteine quartile compared with the lowest (30) .…”
Section: Evidence From Observational Studiesmentioning
confidence: 95%
“…In the past decade, numerous large observational studies have provided evidence to support a role for homocysteine and/or low B-vitamin status in fracture risk (Table 1) (12,(29)(30)(31)(32)(33)(34)(35)(36)(37) . In 2004, two landmark studies performed in the Netherlands and the USA produced consistent findings in terms of the magnitude of increased risk of fracture associated with mild elevations in homocysteine (36,37) .…”
Section: Evidence From Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, moderate hyperhomocysteinemia induced by low folate status is an independent risk factor for cardiovascular disease (CVD) (Ishihara et al 2008; Bentley et al 2009), stroke (Yang et al 2006; Huo et al 2015; Li et al 2016b), colon cancer (Bentley et al 2009), dementia (Jernerén et al 2015), fracture (Gjesdal et al 2007), kidney diseases (Massy 2003) and depression (Bottiglieri 2005; Hiraoka et al 2014). These diseases can be prevented or alleviated by increased folate intake, as shown by many epidemiological and interventional studies.…”
Section: Diseases Prevented By Folic Acid Fortificationmentioning
confidence: 99%
“…In contrast, the TT genotype of MTHFR C677T showed significantly lower serum folate and higher serum Hcy than the CC and CT genotypes (Hiraoka et al 2004). The TT genotype of the C677T polymorphism in MTHFR has been associated with CVD (Morita et al 1998), dementia (Kageyama et al 2008), osteoporosis (Gjesdal et al 2007), depression (Bottiglieri 2005) and kidney diseases (Sakamoto et al 2015). In addition, there are many risk SNPs of CVD, metabolic syndrome, and other chronic diseases (Kagawa 2012; Kagawa et al 2012) that affect the MTHFR genotypes and must be considered for disease prevention and the reduction of medical costs.…”
Section: Genetic Polymorphisms Of Folate Metabolismmentioning
confidence: 99%